(untitled) (Nepal Medical College Journal, 2021)
The main aim of this study was to find an alternative method to type the urinary stones, which do not comply with the available method. For this study 100 stones were selected and were analysed by wet chemical method. The compositions of randomly selected 10 stones each among the stones typed based on the available and the new method were crosschecked by Fourier Transform infrared Spectroscopy (FTIR) method. Among the 100 stones, 46 stones were of Category I [21 stones Uric acid/Urate, 13 stones Oxalate, 12 stones Phosphate] while five were of Category II stones. Rest 49 stones, which cannot be typed by the available method, were typed by considering the ratios between the characterizing and indicating anions. To type the Oxalate stones, Oxalate to Urate ratio between 16.8:1 and 67.7:1; Urate stones, Urate to Oxalate ratio between 0.7:1 and 101.7:1 and Non- infection Phosphate stones, Phosphate to Oxalate ratio between 0.4:1 and 24.4:1 were considered. Based on the newly proposed method majority of the stones were of Oxalate type (n=41). Based on both the methods of stone typing, of the total 100 stones, 54 stones were Oxalate type, 25 stones were Uric acid/Urate type, 16 stones were Non-infectious Phosphate stones and 05 were Infectious stones. The compositions of the randomly selected ten stones of each typed from the available and the newly proposed method were similar to the results obtained by FTIR method. This study indicated that, the new method could be used as an alternative method to type the stones.